Welfare Dynamics Measurement : Two Definitions of a Vulnerability Line and Their Empirical Application - Dang, Hai-Anh H.; Lanjouw, Peter F. (World Bank, Washington, DC, 2014)
Little research currently exists on a vulnerability line that distinguishes the poor population from the population that is not poor but that still faces significant risk of falling back into poverty. This paper attempts to fill this gap by proposing vulnerability lines that can be straightforwardly estimated with panel or cross-sectional household survey data, in rich- and poor-country settings. These vulnerability lines offer a means to broaden traditional poverty analysis and can also assist with the identification of the middle class or resilient population groups. Empirical illustrations are provided using panel data from the United States (Panel Study of Income Dynamics) and Vietnam (Vietnam Household Living Standards Survey) for the period 2004-2008 and cross-sectional data from India (National Sample Survey) for the period 2004-2009. The estimation results indicate that in Vietnam and India during this time period, the population living in poverty and the middle class have been falling and expanding, respectively, while the opposite has been occurring in the United States.